2007
DOI: 10.1038/sj.jcbfm.9600514
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of S. Pneumoniae Bacteremia on Cerebral Blood Flow Autoregulation in Rats

Abstract: In the present study, we studied the effect of bacteremia on cerebral blood flow (CBF) autoregulation in a rat model of pneumococcal bacteremia and meningitis. Anesthetized rats were divided into five groups (A to E) and inoculated with pneumococci intravenously and normal saline intracisternally (group A, N = 10); saline intravenously and pneumococci intracisternally (group B, N = 10); pneumococci intravenously and pneumococci intracisternally (group C, N = 5); saline intravenously, antipneumococcal antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Autoregulation of CBF is a sensitive mechanism, which can be impaired by various pathological conditions, and has a direct impact on delayed ischemic events and poor outcome [50,51]. Although cerebral autoregulation was maintained in several experimental models of sepsis [39,44,52,53], most patients with septic shock had impaired cerebral autoregulation in our study. We found only three human studies that have previously evaluated cerebral autoregulation in septic patients, and these yielded conflicting results.…”
Section: Discussionmentioning
confidence: 90%
“…Autoregulation of CBF is a sensitive mechanism, which can be impaired by various pathological conditions, and has a direct impact on delayed ischemic events and poor outcome [50,51]. Although cerebral autoregulation was maintained in several experimental models of sepsis [39,44,52,53], most patients with septic shock had impaired cerebral autoregulation in our study. We found only three human studies that have previously evaluated cerebral autoregulation in septic patients, and these yielded conflicting results.…”
Section: Discussionmentioning
confidence: 90%
“…We have previously demonstrated an important role of accompanying bacteremia in experimental pneumococcal meningitis for both mortality [4] and brain pathophysiology (attenuated CSF pleocytosis [2], increased cerebral perfusion pressure and mean arterial pressure as well as an interrupted cerebral autoregulation [3], increased hippocampal apoptosis [5] and increased brain ventricle size, BBB leakage, and white matter apparent diffusion coefficient (ADC) [6]). As described above, there was a positive correlation between hippocampal ADC-values and size of brain ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied the role of accompanying bacteremia in detail in experimental pneumococcal meningitis and have demonstrated that this complication resulted in an attenuated CSF pleocytosis [2], an interrupted cerebral autoregulation [3], and an increased mortality [4] as well as hippocampal apoptosis [5]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest a possible third, earlier, IL-10-repressible mechanism of neuronal damage, which may precede pneumococcal invasion of the CNS (358). Additionally, in the setting of experimental meningitis, bacteremia has been shown to contribute not only to increased hippocampal apoptosis but also to dysregulation of CBF autoregulation, reduced meningeal inflammation, and attenuated CSF pleocytosis (366,380). The mechanisms involved remain largely unclear.…”
Section: Sepsis and Hippocampal Damagementioning
confidence: 97%